Comparison of CT and MRI for contouring active bone marrow in bone marrow sparing IMRT of carcinoma cervix and its effects on functional outcomes. (November 2022) - Sajeevan, Sanjay; Singh, Pragya; Krishnan, Ajay; Singh, Sumit; Gupta, Sweety; Sharma, Pankaj; Pasricha, Rajesh; Joseph, Deepa; Narayan, Manishi L.; Gupta, Manoj
Highlights: Intensity-modulated radiotherapy (IMRT) has been used to reduce dose to bone marrow (BM) irradiation during pelvic conformal radiotherapy. Computed tomography (CT) and magnetic resonance imaging (MRI) were compared for contouring bone marrow to spare functional bone marrow for Intensity-modulated radiotherapy (IMRT) in carcinoma cervix. There was no significant difference in two groups in Bone Marrow Volume. Mean value of V10, V20, V30 and V40 all were lower in group II (MRI) but the differences in volume were not significant. Abstract: Objective: Intensity-modulated radiotherapy (IMRT) has been used to reduce dose to bone marrow (BM) irradiation during pelvic conformal radiotherapy by contouring bone marrow and sparing it during radiotherapy planning. The present study was done to compare CT & MRI for contouring bone marrow to spare functional bone marrow for Intensity-modulated radiotherapy (IMRT) in carcinoma cervix and to assess its effect on functional outcome. Material & methods: This prospective, observational study included newly diagnosed carcinoma cervix patients treated by radical chemoradiation. Patients were distributed in two arms i.e. CT arm and MRI for contouring bone marrow. Regions taken into consideration for bone marrow volumes contouring were 4th and 5th Lumbar vertebrae, whole pelvis and proximal femur upto lesser trochanter. In CT arm bone marrow regions were contoured using freehand method with window adjusted to bone range (Window – 2500/ Level – 400) and in MRI arm BM regions on the MR images that had pixel values similar to muscle or IDEAL IQ sequence based on fat fractions present in bone marrow (BM) was used to contour. Results: 17 patients in CT arm and 19 patients in MRI arm were included. There was no significant difference between the groups in terms of Bone Marrow Volume (cm 3 ) (W = 171.500, p = 0.763). The mean value of V10, V20, V30 and V40 all were lower in group II (MRI) but the differences in volume were not significant. Bone marrow V30 in CT arm was found to correlate with absolute neutrophil count drop which was statistically significant in univariate (Coefficient – 1.00 [0.14–2.01, p = 0.025] and multivariate analysis (Coefficient – [1.08 (0.14 to 2.01, p = 0.025]). Bone marrow V30 in MRI arm was found to correlate with total leucocyte count percentage drop, which on multivariate analysis was statistically significant (Coefficient – 1.29 [0.29–2.28, p = 0.013]). Conclusions: Dosimetric parameters of bone marrow V10 and V30 were found to be associated with absolute neutrophil and total leucocyte nadir respectively. Haematological toxicity was observed more in MRI arm but more propspective studies are required for further validation.